Neuroprotective effects of pretreatment with macrolide antibiotics on cerebral ischemia reperfusion injury. (25th May 2015) - Inaba, Toshiki; Katayama, Yasuo; Ueda, Masayuki; Nito, Chikako
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: This study aims to determine if macrolide antibiotics have neuroprotective effects against transient cerebral ischemia. Methods: Sprague-Dawley rats were subjected to cerebral ischemia for 90 minutes followed by 24 or 72 hours of reperfusion. An oral suspension of roxithromycin (RXM), clarithromycin (CAM), erythromycin (EM), azithromycin (AZM), or kitasamycin (INN) was given at 10 or 100 mg/kg for 7 days before ischemia. The infarct volume, edema volume, and neurological performance were evaluated after 24 and 72 hours of reperfusion. The cerebral blood flow (CBF) was measured with a magnetic resonance imaging (MRI) system after 90 minutes of ischemia. Another experiment was conducted to investigate how the ischemic injury was affected by the interval from the antibiotic pretreatment to the ischemia in rats pretreated with CAM. Results: Roxithromycin, CAM, AZM, and INN significantly reduced the infarct volume in the high-dose group after 24 and 72 hours of reperfusion. All of the agents significantly decreased the edema in the high-dose groups at 24 and 72 hours, while only CAM and AZM significantly reduced the edema volume in the low-dose groups at 24 hours. All of the macrolide antibiotics at the high dose significantly improved neurological deficit scores at 24 and 72 hours. There were no differences in the CBF between the vehicle and respective antibiotic groups. In the experiment examining the interval, the 24-hour interval group exhibited the strongest neuroprotective effect. Discussion: These results demonstrate that the macrolide antibiotics RXM, CAM, EM, AZM, and INN may confer neuroprotective effects against ischemic damage following cerebral ischemia without affecting the CBF.